2012
DOI: 10.1111/j.1468-2850.2012.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

How consistent are clinical significance classifications when calculation methods and outcome measures differ?

Abstract: Outcome studies report the percentage of clinically significant outcomes; however, the reliability of these classifications is unclear. The current study explored the extent to which inconsistencies arise in classifying patient outcomes using five clinical significance calculation methods and three outcome measures. Adult inpatients (N = 2,676) treated for depression completed the three outcome measures pre-and post-treatment. Their outcomes were classified as recovered, improved, unchanged, or deteriorated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…As Ronk et al (2012) have argued, categorizations of clients following treatment can differ greatly across outcome measures, and therefore clinicians need to make explicit reference to the psychological construct that a measurement instrument purports to measure. That is, if a person is recovered in terms of anxiety, this does not mean they are recovered in an absolute sense.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Ronk et al (2012) have argued, categorizations of clients following treatment can differ greatly across outcome measures, and therefore clinicians need to make explicit reference to the psychological construct that a measurement instrument purports to measure. That is, if a person is recovered in terms of anxiety, this does not mean they are recovered in an absolute sense.…”
Section: Discussionmentioning
confidence: 99%
“…The DASS-21 is a 21-item self-report scale that purports to measure levels of depression, stress, and anxiety in the population. Each seven-item scale has ' Other studies that have extracted data from a similar time period include Byrne, Hooke, and Page (2010); Newnham et al (2007); and Ronk et al (2012). four response options ranging from 0 (did not apply to me at all) to 3 (applied to me much, or most of the time). A maximum score of 42 (i.e., each scale is multiplied by 2 to make scores comparable to the DASS-42) on each scale indicates elevated depression, anxiety, or stress.…”
Section: Methodsmentioning
confidence: 99%
“…Ronk, Hooke and Page (2012) concluded that four of the five methods they compared (one of them was the original JT method) yielded similar outcome classifications with a mean agreement of 93.7%. Thus, there is general consensus regarding the appropriateness of the original JT method (Atkins et al, 2005;Ogles, Lunnen, & Bonesteel, 2001;Wise, 2004).…”
mentioning
confidence: 92%
“…The following information was extracted from the articles: 1) primary outcome variable; 2) type of intervention; 3) result of the statistical significance of the pre-post change (either raw or relative to a control group); 4) use or nonuse of the RCI statistic; 5) use or nonuse of a cutoff for moving closer to the functional population; 6) if a cutoff was adopted, which cutoff was applied; 7) method of summarizing the individual level statistics; and 8) inclusion/non-inclusion of an effect size if a summary statistic was utilized. Although Ronk, Hooke and Page (2012) highlight the importance of the selection of an appropriate outcome measure when conducting clinical significance analyses, given the wide variety of treatment outcomes and treatment outcome measures, we limited our investigation to only the primary outcome measure in each study.…”
Section: Literature Review 1: Jt Methodsmentioning
confidence: 99%